(untitled) (Cultura Económica, 2019)
In the present study, the author claims that the conceptual, methodological and practical choices involved in any poverty measurement exercise have consequences on the estimated magnitude, depth and structure of poverty. Nevertheless, these options are not always explicit. The 2010 Iraqi Poverty Report, published by the World Bank, represents an exception in this sense. The author uses this case to explore in detail the underlying options in the welfare indicator, the poverty line and the poverty measures, showing the importance of making these choices explicit.